Embryonal Rhabdomyosarcoma in Mastoid and Middle Ear in a 3-Year-Old Girl: A Rare Case Report - Saman Vegari; Alireza Hemati; Hosein Baybordi; Leila Davarimajd; Ghasem Chatrbahr (Case Reports in Otolaryngology)
Introduction. The most common sarcoma of childhood is rhabdomyosarcoma, approximately 35% of all paediatric rhabdomyosarcomas occur in the head and neck. Case Report. A 3-year-old girl referred to our clinic due to serosanguineous purulent discharge from her right ear. After paraclinical and pathologic evaluation it was diagnosed as embryonic rhabdomyosarcoma. Conclusions. In all children with mastoiditis, especially in young children, rhabdomyosarcoma should be considered as a differential diagnosis.